Environmental Impact of Wine Aging Process in Oak Barrels in Wineries of La Rioja (Spain) - J. Flor, Francisco (2018)
Abstract: The primary objective of winemaking companies is to produce quality wines, with aging playing a fundamental role in the vinification process. This paper presents a gate-to-gate life cycle analysis of the productive processes involved in aging one liter of wine in Quercus alba and Quercus petraea oak barrels for six months. The research was undertaken using 225 L, 300 L, and 500 L barrels. In the Global Warming-GWP100 category of impact, aging in 225-L barrels has an environmental impact of 3.27 kg CO eq./L of wine for every liter aged for six months in Q. alba and 3.18 E-02 kg CO 2 2 eq./L of wine for Q. petraea. The same aging in 300-L and 500-L barrels has environmental impacts of 2.21 kg CO 2 eq./L of wine and 1.58E-02 kg CO eq./L of wine, respectively, for Q. alba. These last values are reduced to 2.18 E-02 kg CO 2 2 eq./L of wine and 1.53 E-02 kg CO eq./L of wine for Q. petraea species.